Yield gap analysis of recommended soybean (Glycine max) production technologies and their impact on energy and carbon budgeting - VERMA, RAKESH KUMAR; BILLORE, SUNIL DATT; M, RAGHAVENDRA (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during rainy (kharif) season of 2017–18 at Research farm of ICAR-IISR, Indore, Madhya Pradesh, to study the effect of different agronomic practices on productivity, energy indices and carbon balance of soybean [Glycine max (L.) Merr.]. The additional use of micronutrients (Zn, B and Mo) and secondary nutrients along with full package of practices showed positive yield effect by 6.08% and 3.20% as compared to whole package. The narrow row planting (30 cm) and 50% RDF + 2% urea spray along with full package of practices had very little negative effect on the yield. On pooled average basis, the deletion of any recommended practice from the full package of practices reduced the yield by 1.14–71.69%. The highest yield reduction was associated with the 50% reduction of seed rate in full package of practices. Energy output followed the similar trend as observed in seed yield. Highest energy use efficiency was recorded with 50% RDF + 2% urea spray. The maximum specific energy and energy profitability was registered under full package of practices + 50% (30 kg/ha) seed rate treatment. Highest carbon use efficiency was registered with full package of practices without RDF. Thus, when comparing the carbon intensity (biomass and seed), the maximum carbon intensity was associated with full package of practices + 50% seed rate.